Deactivation of Contaminated Metal Surfaces by Means of Pulsed Laser Systems - V. P. Khantov; K. V. Sergeyev; V. V. Osipov; O. A. Rachkova; E. F. Egorov (Вестник войск РХБ защиты, 2025)
HighlightsIt is necessary to improve methods that permit to eliminate radioactive substances from surfaces that are being contaminated as a result of nuclear industry activity.Relevance. In the course of development, conventional decontamination methods have reached their potential technological limit and nowadays may not totally meet the needs of Russian NBC Protection Troops in technological technical, economic and ecological aspects.Purpose of the study is to evaluate advantages of laser electromagnetic emission in terms of contaminated surfaces deactivation.Materials and methods. The authors of this paper have analyzed the English language sources available on Google Scholar. Particular–to general analysis was employed. The article has addressed electromagnetic emission laws.Discussion. The essence of thermal decontamination methods is that contaminated surface is treated with energy flows of high intensity in the form of infrared light emissions or hyperthermal gas flow, etc. This is the basic premise for deactivation of items by hyperthermal impact or electromagnetic emission to be exact. It should emphasized that deactivation by laser permits to decrease radiation burden for military personnel as well as helps to return to production expensive equipment used to eliminated the consequences of technological disasters. Considering the mentioned above, we should think over the possibility and necessity of use of lasers to decontaminate armaments and military and special purpose equipment. The optical fiber lasers can be easily integrated into processing lines for decontamination devices due to the fact that a laser beam can go along optic fiber at a distance of several tens of meters without losing power. There are no adjustable knots and expendable materials in optical fiber lasers, that is why they are very reliable and efficient.Conclusions. Modern optical fiber lasers have small dimensions, low power consumption and low weight. They don’t require special climatic or air clarity conditions that is why they are supposed to be easily integrated into processing lines for decontamination devices.